Fotografía, memoria y desaparición forzada de personas en Chile (1973-1990) - Juan Pablo Silva-Escobar (Caravelle)
The purpose of this paper is to analyze the relationship between photography, memory, and state violence. To this end, two photographs will be analyzed in which we see the relatives of the detained-disappeared of the Pinochet dictatorship demanding justice, the appearance and reparation of their loved ones in the public space. I argue that these images not only contribute to the legibility of this painful history, but they also help understand the way in which Pinochet's dictatorship was configured as necropolitics, that is, as a form of government that decides who may live and who must die.